Enhancing the Performance of Quantum Dot Light-Emitting Diodes Using Solution-Processable Highly Conductive Spinel Structure CuCo2O4 Hole Injection Layer - Park, Min Ho; Kim, Min Gye; Ma, Jin Hyun; Jeong, Jun Hyung; Ha, Hyoun Ji; Wonsik Kim; Park, Soohyung; Kang, Seong Jun (MDPI Open Access Publishing, 2023)
Charge imbalance in quantum-dot light-emitting diodes (QLEDs) causes emission degradation. Therefore, many studies focused on improving hole injection into the QLEDs-emitting layer owing to lower hole conductivity compared to electron conductivity. Herein, CuCo2O4 has a relatively higher hole conductivity than other binary oxides and can induce an improved charge balance. As the annealing temperature decreases, the valence band maximum (VBM) of CuCo2O4 shifts away from the Fermi energy level (E-F), resulting in an enhanced hole injection through better energy level alignment with hole transport layer. The maximum luminance and current efficiency of the CuCo2O4 hole injection layer (HIL) of the QLED were measured as 93,607 cd/m(2) and 11.14 cd/A, respectively, resulting in a 656% improvement in luminous performance of QLEDs compared to conventional metal oxide HIL-based QLEDs. These results demonstrate that the electrical properties of CuCo2O4 can be improved by adjusting the annealing temperature, suggesting that solution-processed spinel can be applied in various optoelectronic devices.